Automated Impaction Angulation Measurement of Mandibular Third Molars for Winter’s Classification Using Deep Learning - Ali, Md. Anas; Fujita, Daisuke; Kishimoto, Hiromitsu; Makihara, Yuna; Noguchi, Kazuma; Kobashi, Syoji (Journal of Advanced Computational Intelligence and Intelligent Informatics, 2025)
Impacted third molar extraction, particularly of mandibular teeth, is a common procedure performed to alleviate pain, infection, and misalignment. Accurate diagnosis and classification of impaction types are crucial for effective treatment planning. This study introduces a novel algorithm for automatically measuring the impaction angles of mandibular third molars (T32 and T17) from orthopantomogram (OPG) images. The proposed method is based on deep learning techniques, including segmentation and key point detection models. It categorizes impactions into Winter’s classification: distoangular, mesioangular, horizontal, vertical, and other on both sides, using the measured angles. The proposed method used 450 OPGs, achieving high mandibular molar segmentation accuracy with dice similarity coefficients (DSC) values of 0.9058–0.9162 and intersection over union (IOU) scores of 0.82–0.84. The object keypoint similarity (OKS) for detecting the four corner points of each molar was 0.82. Angle measurement analysis showed 80% accuracy within ±5° deviation for distoangular impaction of T32 and within ±8° for T17. The F1-scores for mesioangular classifications were 0.88 for T32 and 0.91 for T17, with varying performance in other categories. Nonetheless, the predicted angles aid in identifying impaction types, showcasing the method’s potential to enhance dental diagnostics and treatment planning.